Leaving the Dark Side? Insights Into the Evolution of Luciferases - Delroisse, Jérôme; Duchatelet, Laurent; Flammang, Patrick; Mallefet, Jérôme (Frontiers in Marine Science, 2021)
Bioluminescence—i.e., the emission of visible light by living organisms—is defined as a biochemical reaction involving, at least, a luciferin substrate, an oxygen derivative, and a specialised luciferase enzyme. In some cases, the enzyme and the substrate are durably associated and form a photoprotein. While this terminology is educatively useful to explain bioluminescence, it gives a false idea that all luminous organisms are using identical or homologous molecular tools to achieve light emission. As usually observed in biology, reality is more complex. To date, at least 11 different luciferins have indeed been discovered, and several non-homologous luciferases lato sensu have been identified which, all together, confirms that bioluminescence emerged independently multiple times during the evolution of living organisms. While some phylogenetically related organisms may use non-homologous luciferases (e.g., at least four convergent luciferases are found in Pancrustacea), it has also been observed that phylogenetically distant organisms may use homologous luciferases (e.g., parallel evolution observed in some cnidarians, tunicates and echinoderms that are sharing a homologous luciferase-based system). The evolution of luciferases then appears puzzling. The present review takes stock of the diversity of known “bioluminescent proteins,” their evolution and potential evolutionary origins. A total of 134 luciferase and photoprotein sequences have been investigated (from 75 species and 11 phyla), and our analyses identified 12 distinct types—defined as a group of homologous bioluminescent proteins. The literature review indicated that genes coding for luciferases and photoproteins have potentially emerged as new genes or have been co-opted from ancestral non-luciferase/photoprotein genes. In this latter case, the homologous gene’s co-options may occur independently in phylogenetically distant organisms.